'Technology, hormones, and stupidity': The affective politics of teenage sexting. (September 2013) - Angelides, Steven
The last several years in Anglophone societies have seen an explosion of anxiety about teenage 'sexting'. Legislators are racing to have laws designed that can keep pace with new technologies and the exchange of sexually explicit material. However, in the absence of laws crafted with sexting in mind, police, parents, and prosecutors in many jurisdictions are sometimes responding by charging some teenagers with child pornography, sexual harassment, and indecency offences. Some of these felonies, even when involving the consensual exchange of self-images to a sexual partner, have resulted in adolescents being mandated to register as sex offenders. This article considers the stakes of current socio-legal and pedagogical responses to the practice of consensual teenage sexting. It argues that, beyond an expression of concern with child protection from harm, a 'sexting panic' is being generated in part as a way of displacing the question of teenage sexual agency.